Experiences of precarious work within higher education institutions: a qualitative evidence synthesis - Solomon, Shihaam; Du Plessis, Marieta (Frontiers in Education, 2023)
To identify and synthesise the best evidence on the experiences of precarious employed academics in high education institutions. A qualitative evidence synthesis was employed, following the Joanna Briggs Institute (JBI) principles. The identified studies were screened by titles and abstracts (n= 308)—full-text (n= 19), employing these inclusion criteria: studies reporting on precarious employment experiences in higher education; part-time or fixed-term academic positions; qualitative studies between 2010 to 2021. A quality appraisal was conducted. Data were extracted while findings from the included studies (n=19) were collated using meta-aggregation with the Joanna Briggs Institute Qualitative Assessment and Review Instrument (JBI-QARI). Ninety-four extracted findings were aggregated into 19 categories and then grouped into five synthesised findings: 1) Precarity is created and perpetuated through structural changes in the global economy and wider higher education landscape; 2) Coping strategies precariously employed academics used to endure precarious employment in higher education; 3) Gendered dimensions shaping employment precarity in academia; 4) Impact of precarious employment on academics; 5) Impact of academic precarity on the university. These precariously employed academics felt overwhelmed, vulnerable, exploited, stressed, anxious, and exhausted with their employment conditions. These circumstances include operating in unstable and insecure employment with no guarantees of permanent employment. The need to reassess policies and practices within higher education institutions is necessary and could offer these precariously employed academics the much-needed support and assistance to combat the effects of precarious employment.